Active Elastic Support/Dry Friction Damper with Piezoelectric Ceramic Actuator - Liao Mingfu; Song Mingbo; Wang Siji (Shock and Vibration)
The basic operation principle of elastic support/dry friction damper in rotor system was introduced and the unbalance response of the rotor with elastic support/dry friction damper was analyzed theoretically. Based on the previous structure using an electromagnet as actuator, an active elastic support/dry friction damper using piezoelectric ceramic actuator was designed and its effectiveness of reducing rotor vibration when rotor traverses its critical speed and blade-out event happened was experimentally verified. The experimental results show that the active elastic support/dry friction damper with piezoelectric ceramic actuator can significantly reduce vibration in rotor system; the vibration amplitude of the rotor in critical speed region decreased more than 2 times, and the active damper can protect the rotor when a blade-out event happened, so the rotor can traverse the critical speed and shut down smoothly. In addition, the structure is much simpler than the previous, the weight was reduced by half and the power consumption was only 5 W.